Doença tálamo-cortical. Análise retrospectiva em cães e trauma experimental em coelhos - Aiello, Graciane (2016)
The purposes of this study were to perform retrospective studies about epilepsy and idiopathic epilepsy in dogs presented at the Veterinary Neurology Service, University Veterinary Hospital, of Federal University of Santa Maria and use a flexible urethral catheter as an alternative method to measuring intracranial pressure in rabbits with head injury and compare the data with ventriculostomy catheter (conventional method) . In the first paper, 66 records of dogs with presumptive diagnosis of epilepsy were selected. 66.7% of them, were epilepsy idiopatic, 21.2% symptomatic and 12.1% probably symptomatic. The mongrel dogs were the most affected and age-group prevailed was one to 5-year-old. The tonic-clonic seizure was the most observed, the main pre-ictal symptom was to try to catch owner´s attention and compulsive walking in the post-ictal period. In the second paper, 21 dogs with idiopatic epilepsy were included; the median age at onset of seizures was 3.4 years, the median number of seizure before the start of treatment was 25.7 and duration of seizure before treatment was 71 days. The phenobarbital was used as monotherapy with dose from 1.4 to 12 mg kg-1 and the median of serum concentration was 26.41 μg kg-1. There was significant reduction in the frequency of the seizure after start the treatment. 19% of dogs were in remission of seizure. In blood analysis, there was increased serum activities of AP (23,81%) and ALT (14,20%), decreased total protein (42,29%), hypoalbuminemia (9,5%) and it was not increased AST activities. The main secondary lesions were liver disease and hypothyroidism. In the third paper, New Zealand rabbits were randomly distributed into two groups, G1: measuring the ICP with ventriculostomy catheter (n=6) and G2: measuring the ICP with urethral catheter (n=6). Two craniotomy were performed in the right and left parietal region for the implantation of the ventriculostomy catheter and/or flexible urethral catheter and epidural 4F Fogarty arterial embolectomy catheter, respectively. MAP, CPP, HR, RF and RT values were measured before and after craniotomy. The ICP value was mensured after craniotomy, ever five minutes during 40 minutes after the balloon was inflated with 0.3 ml of NaCl 0.9% and more 40 minutes after the balloon was inflated with 0.6 ml. The ICP value increased in both groups, however, the ICP values were lower in the rabbits measured with flexible urethral catheter. The flexible urethral catheter can be used as alternative method to measure ICP values im rabbits with head injury.